Determinants of Rural-Urban Disparities in Surgical Treatment Accessibility for Carpal Tunnel Syndrome: Surgical Treatment Accessibility for Carpal Tunnel Syndrome - Qazi, Farhan; Arif, Muhammad; Chugthai, Aneeqa; Bhatti, Zahid Iqbal; Ahmed, Nisar; Mustafa, Hussain (Pakistan Journal of Health Sciences, 2024)
Carpal Tunnel Syndrome is a common neuropathic condition that causes pain, numbness, and weakness in the affected hand. Objective: To investigate the determinants of surgical treatment accessibility for Carpal Tunnel Syndrome. Methods: For this purpose, a prospective cohort study study was carried out at a tertiary care hospital in Pakistan. The research included 284 patients diagnosed with Carpal Tunnel Syndrome who were suggested for surgery. Data were collected using a structured questionnaire, focusing on demographic factors, socioeconomic status, and healthcare system-related questions. Descriptive statistics was performed using SPSS version 26.0 to calculate means ± standard deviations for all the continuous variables, and chi-square tests for categorical variables. Results: Results show that most of the patients (57.75%) in the study belong to rural areas, and 42.25% of patients belong to urban areas. A multivariable logistic regression shows that living in a rural area was significantly linked with older age and body mass index. Conclusions: It was concluded that people living in rural areas of Pakistan are deprived of surgical treatment for Carpal Tunnel Syndrome. Other associated factors that contribute to the poor accessibility of surgical treatment of the disease are older age and body mass index.